2017
DOI: 10.1080/10826084.2016.1267223
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Cognitive Enhancement in Greek University Students: Differences Between Users and Non-Users in Social Cognitive Variables, Burnout, and Engagement

Abstract: Although there are some studies about PCE prevalence, it is less clear how users and nonusers of PCE substances differ with respect to their positive and negative student experiences (e.g., academic burnout, engagement with studies) and in social cognitive variables that relate to decision-making and self-regulation of PCE use. The present study assessed whether students with different experiences of PCE substance use displayed differences in academic burnout, study engagement and social cognitive variables re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…This finding resembles several prior studies on different substances specific or unspecific to CE (Brown et al, ; Lazuras et al, ; Maier, Haug, & Schaub, ; Middendorff et al, ; Peck et al, ; Schröder et al, ; Wolff & Brand, ). However, some studies found no effects of different indicators for stress (Lazuras et al, ; Maier, Haug, & Schaub, ). The finding of this study could be understood from different theoretical perspectives (e.g., self‐medication hypothesis, stress coping, strain theory, and the job demands–resources theory).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding resembles several prior studies on different substances specific or unspecific to CE (Brown et al, ; Lazuras et al, ; Maier, Haug, & Schaub, ; Middendorff et al, ; Peck et al, ; Schröder et al, ; Wolff & Brand, ). However, some studies found no effects of different indicators for stress (Lazuras et al, ; Maier, Haug, & Schaub, ). The finding of this study could be understood from different theoretical perspectives (e.g., self‐medication hypothesis, stress coping, strain theory, and the job demands–resources theory).…”
Section: Discussionsupporting
confidence: 90%
“…We found that higher levels of stress are positively associated with the likelihood of self-reporting such use. This finding resembles several prior studies on different substances specific or unspecific to CE (Brown et al, 2014;Lazuras et al, 2017;Maier, Haug, & Schaub, 2015;Middendorff et al, 2012;Peck et al, 2018;Schröder et al, 2015;Wolff & Brand, 2013). However, some studies found no effects of different indicators for stress (Lazuras et al, 2017;Maier, Haug, & Schaub, 2015).…”
Section: Perceived Stresssupporting
confidence: 90%
See 3 more Smart Citations